Malting of preharvest sprouted wheat - Carvalho, Paulo; Beléia, Adelaide (Revista Ciência Agronômica, 2019)
Pre-harvest sprouting is one of the most important problems of the wheat crop and it is necessary to find alternative uses for the grain because millers reject the damaged wheat. In the field these grains were stimulated to germinate, due to weather conditions  and their metabolic activity was enhanced, the hydrolytic enzymes promoted changes in the proteins and reserve carbohydrates, which reflect on the flour quality. Similar to malting germination has started, but with different intensity and under different conditions. There are some studies about malting of sprouted barley and the malting of rain-damaged wheat could be a possibility worth investigation. The objective of this work was to evaluate the malting of pre-harvest sprouted wheat samples. Four wheat samples were characterized by falling number and germination power; and three of them that were considered sprouted. A randomized standard experimental design was applied and the malting conditions were: moisture content 43%, germination time 78 hours, and germination temperature 12.5 oC. Malt quality parameters determined were: malting losses, extract, limit attenuation, viscosity, total protein, soluble protein, Kolbach index, alfa and beta-amylase. The malting process resulted in increased soluble protein, FAN, Kolbach index and α-amylase activity, but decreased β-amylase activity for all rain damaged samples. There was no difference among the rain damaged samples for FAN, Kolbach index, α and β-amylase activity, extract, apparent attenuation limit and viscosity. A sound sample malted had higher α and β-amylase activity, extract, and the lowest soluble protein content.